ESTETIKA TEMATIS-METAFORIS PADA LIRIK LAGU ‘KAU SEPUTIH MELATI’ DAN ‘TIADA NAMA, SEINDAH NAMAMU’: PERSPEKTIF LINGUISTIK SISTEMIK FUNGSIONAL - Endang Yuliani Rahayu; Katharina Rustipa; Teguh Kasprabowo; Yulistiyanti, Yulistiyanti (LPSDI Bina Patria, 2024)
Old songs (of 1980s) linger without limit of time. Seniors at their 50s, for sure, like such songs to bring back the past memories of various feelings, which, for some, have been made ‘Skeleton in the cupboard.’ Such a phenomenon does not occur without reasons. Old songs still maintain tight principles of literary esthetics through thematic structure and metaphoric uses. The current study investigated thematic-metaphoric esthetics in two song lyrics entitled Kau Seputih Melati written by Jockie Suryo Prayogo and sung by Dian Permana Poetra, and Tiada Nama Seindah Namau, written by Obbie Messakh and sung by Ratih Purwasih, two of the favorite singers of 1980s. In order to collect the data, the listening and taking note method were applied in this research. The song lyrics assumed to employ well-structured-themes and metaphors as esthetic devises were purposefully taken for descriptive, qualitative and interpretative analysis. UAMCT.6 Application of Systemic Functional Linguistics (SFL) was used in componential analysis on the use of metaphors as well as reffering to Systemic FunctionLinguistic by Halliday. The findings indicate that thematic-metaphoric esthetics are thematic structure and the use of metaphors which can arouse ‘human’s latent sense of beauty’ seen from the consistency and uniqueness of theme-rheme structure and the types, meanings and functions of the metaphors in words, phrases or sentences. The findings were thoroughly discussed to justify that old songs of 1980s maintained the values of literary esthetics apart from the social values to enhance the teaching of literature, especially Indonesian literature.This research concludes that the consistency of theme rheme found in both songs contribute to the song esthetic meanwhile the use of metaphors in forms of words, phrases, clauses which are are aligned and balanced also contribute to song aesthetic related to the imagination both from the singer and listeners